Patterns of Knowledge Construction - Bo Chang (Adult Education Research Conference, 2009)
Based on Berger & Luckmann’s (1967) social constructionism framework, the purpose of this study is to identify the knowledge construction patterns and the conditions for these patterns to occur in a learning community in Shanghai, China.